Genetic Analysis of Citrobacter sp.86 Reveals Involvement of Corrinoids in Chlordecone and Lindane Biotransformations - Barbance, Agnès; Della-Negra, Oriane; Chaussonnerie, Sébastien; Delmas, Valérie; Muselet, Delphine; Ugarte, Edgardo; Saaidi, Pierre-Loïc; Weissenbach, Jean; Fischer, Cécile; Le Paslier, Denis; Fonknechten, Nuria (Frontiers in Microbiology, 2020)
Chlordecone (Kepone®) and γ-hexachlorocyclohexane (γ-HCH or lindane) have been used for decades in the French West Indies resulting in long-term soil and water pollution. In a previous work, we have identified a new Citrobacter species (sp.86) that is able to transform chlordecone into numerous products under anaerobic conditions. No homologs to known reductive dehalogenases or other candidate genes were found in the genome sequence of Citrobacter sp.86. However, a complete anaerobic pathway for cobalamin biosynthesis was identified. In this study, we investigated whether cobalamin or intermediates of cobalamin biosynthesis were required for chlordecone microbiological transformation. For this purpose, we constructed a set of four Citrobacter sp.86 mutant strains defective in several genes belonging to the anaerobic cobalamin biosynthesis pathway. We monitored chlordecone and its transformation products during long-term incubation in liquid cultures under anaerobic conditions. Chlordecone transformation products were detected in the case of cobalamin-producing Citrobacter sp.86 wild-type strain but also in the case of mutants able to produce corrinoids devoid of lower ligand. In contrast, mutants unable to insert the cobalt atom in precorrin-2 did not induce any transformation of chlordecone. In addition, it was found that lindane, previously shown to be anaerobically transformed by Citrobacter freundii without evidence of a mechanism, was also degraded in the presence of the wild-type strain of Citrobacter sp.86. The lindane degradation abilities of the various Citrobacter sp.86 mutant strains paralleled chlordecone transformation. The present study shows the involvement of cobalt-containing corrinoids in the microbial degradation of chlorinated compounds with different chemical structures. Their increased production in contaminated environments could accelerate the decontamination processes.